2004
DOI: 10.1183/09031936.04.00080303
|View full text |Cite
|
Sign up to set email alerts
|

STAT4 activation in smokers and patients with chronic obstructive pulmonary disease

Abstract: Activation of the transcription factor signal transducer and activator of transcription (STAT)-4 is critical for the differentiation of T-helper 1 cells/type-1 cytotoxic T-cells and the production of interferon (IFN)-c.Expression of STAT4, phospho-STAT4, IFN-c and T-box expressed in T-cells (Tbet) proteins in bronchial biopsies and bronchoalveolar lavage (BAL)-derived lymphocytes, obtained from 12 smokers with mild/moderate chronic obstructive pulmonary disease (COPD) (forced expiratory volume in one second (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
87
1
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 37 publications
14
87
1
7
Order By: Relevance
“…The reason for this IFN-γ production is not clear at present but is likely to reflect ongoing immune response towards microbial agents although arguments also exist to support auto-immune mechanisms [7]. Our results are in keeping with those of Di Stefano et al who reported greater IFN-γ expression in bronchial biopsies of COPD patients [11].…”
Section: Discussionsupporting
confidence: 90%
“…The reason for this IFN-γ production is not clear at present but is likely to reflect ongoing immune response towards microbial agents although arguments also exist to support auto-immune mechanisms [7]. Our results are in keeping with those of Di Stefano et al who reported greater IFN-γ expression in bronchial biopsies of COPD patients [11].…”
Section: Discussionsupporting
confidence: 90%
“…2B) also appear to be an unprecedented finding and a possible result of the power afforded by study of comparatively greater subject numbers. Moreover, this particular observation is also consistent with previous findings of increased activations of in situ T cells within COPD lungs (2,3,7,9). Proportions of circulating CD4 T cells were also seen here to decrease among those more severe COPD (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…A growing body of evidence suggests that adaptive immune responses play an important role in the pathogenesis and progression of COPD, as evidenced by correlations of lung histological and morphometric measurements with the characteristics of intrapulmonary lymphocyte infiltrations (2)(3)(4)(5)(6)(7)(8)(9)(10). Moreover, activated T cells can cause a variety of the tissue injuries that typify COPD by direct cytopathic effects, elaboration of diverse proinflammatory and deleterious mediators, and/or recruitment and activation of other immune and parenchymal effector cells (11,12).…”
Section: Hronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%
“…Hogg and colleagues (8) reported an association between disease severity and small airways containing CD4 ϩ T cells. In bronchial biopsies from patients with mild to moderate COPD, Di Stefano and colleagues (26) reported an increase in IFN-␥ and signal transducer and activator of transcription 4 (STAT4)-expressing cells as compared with control samples. Nuclear STAT4 expression was mostly found in the CD4 ϩ rather than CD8 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%